Pleurothallis adventurae (Orchidaceae: Pleurothallidinae), eine neue Art aus einer unerforschten Region in Costa Rica - Karremans Lok, Adam Philip (2011)
A new species, Pleurothallis adventurae is illustrated and described from an unexplored region in southern Costa Rica. This species belongs to a small group of mostly South American species with, glaucous, dark green, long, narrow leaves, with revolute margins. It is most closely related to the Ecuadorian P. portillae from which it differs in the shape of the leaf, the color of flowers, the flower indumentum and the width of the petals. It is also related to P. dibolia, P. calamifolia, P. omoglossa and P. sigynes.